An Evaluation of the Functional Potential of Beverages Made from Regional Plant Matrices - Carolina Antonella Paulino; Facundo Carlos Namor (Biology and Life Sciences Forum)
The Argentine Patagonian region provides abundant plant-based materials for functional foods. This study evaluated the functional potential of tisanes made with black tea (BT) or rooibos (R) and Patagonian matrices (blueberry, rosehip, yacón), analyzing total phenols (TPs), flavonoids (Fvs), antioxidant activity (AA), sodium (Na), and potassium (K) content. Tisanes were prepared using 3 g/200 mL of water at 90 °C, with BT or R accounting for 40% of the dry mass and the remaining ingredients contributing 20% each. TPs (67 mg GAE/100 mL) and Fvs (35–42 mg/cup) contributed significantly to dietary intake. Sugar addition reduced bioactive compounds and AA, while sweeteners showed no significant impact. BT-based tisanes were low in sodium, while R-based tisanes had higher levels.